Cyanine dyes: synergistic action of hydrogen, halogen and chalcogen bonds allows discrete I42− anions in crystals. (29th March 2018) - Konidaris, Konstantis F.; Pilati, Tullio; Terraneo, Giancarlo; Politzer, Peter; Murray, Jane S.; Scilabra, Patrick; Resnati, Giuseppe
Abstract : Discrete tetraiodide dianions (I4 2− ) are formed in crystals via halogen bond coordination of I2 by iodide anions which are pinned in their positions by a network of hydrogen bonds involving a benzoselenazole cyanine dye. Abstract : In crystals of a benzoselenazole dye, a network of hydrogen bonds with the dye cations locks two iodide anions at a distance allowing for an iodine molecule to be pinned at either ends via two halogen bonds. I4 2− supramolecular anions are formed as discrete species that lie in the confined space defined by cation molecules.